Comprehensive analysis of college students' autonomous fitness behavior: a narrative review - Gao, Zhendong; Chee, Chen Soon; Omar Dev, Roxana Dev; Gao, Jianhong (Frontiers Media, 2024)
Although the physical health of college students is increasingly receiving attention, their autonomous fitness behavior has not been thoroughly investigated. This narrative review conducted a comprehensive literature search through databases such as PubMed, PsycINFO, Web of Science, and the China National Knowledge Infrastructure (CNKI), reviewing studies published up to December 2023. We explored the constructs of autonomy, fitness behavior, and agency, and discussed their integration within the autonomous fitness model. Our findings indicate a lack of comprehensive studies exploring the multifaceted factors influencing autonomous fitness behaviors. Future research should strive to deepen conceptual understanding and further explore the complex dynamics of the transition from autonomy to persistence, employing technological and interdisciplinary methodological perspectives to enhance understanding and promote sustainable fitness habits.